Respuesta :
Answer:
Final result :
(7x - 6) • (3x2 - 4x + 5)
Step-by-step explanation:
Final result :
(7x - 6) • (3x2 - 4x + 5)
Step by step solution :
Step 1 :
Equation at the end of step 1 :
(7x - 6) • ((3x2 - 4x) + 5)
Step 2 :
Trying to factor by splitting the middle term
2.1 Factoring 3x2-4x+5
The first term is, 3x2 its coefficient is 3 .
The middle term is, -4x its coefficient is -4 .
The last term, "the constant", is +5
Step-1 : Multiply the coefficient of the first term by the constant 3 • 5 = 15
Step-2 : Find two factors of 15 whose sum equals the coefficient of the middle term, which is -4 .
-15 + -1 = -16
-5 + -3 = -8
-3 + -5 = -8
-1 + -15 = -16
1 + 15 = 16
3 + 5 = 8
5 + 3 = 8
15 + 1 = 16
Observation : No two such factors can be found !!
Conclusion : Trinomial can not be factored
Final result :
(7x - 6) • (3x2 - 4x + 5)